The The Influence of Organizational Culture, Work Environment, and Motivation on Job Satisfaction at Badan Pengelola Aset Daerah Provinsi DKI Jakarta - Nina Nurhasanah; Billy Lazuardi; Moh. Rizal Ngambah Sagara (Research Synergy Foundation, 2022)
Human resources are important for the success of the organization or company. Because people are living assets that must be maintained and developed, it is intended to ensure that human resources working in the local government can provide optimal contributions to efforts to achieve their goals. One of the goals of the local government is to create a job satisfaction that the job satisfaction is job satisfaction that reflects the sense of the employee for his work. So you can dilute it to what he does. This study should not only affect organizational culture and working environments but as well as motivation to work directly from the local government of DKI Jakarta. We used sampling technology to use the amount of 96 respondents in the population of 126 employees. In this study, a quantitative approach was used using a quantitative correlation study method. A correlation study has the same meaning as an association study and uses multiple regression methods. The work environment ttest obtained a tcount of 3.988 and a ttable of 1.6616, so in the BPAD DKI of Jakarta province, the work environment (X2) has a significant effect in part on the job satisfaction of the employees. Since the value of tcount is 4.671 and the ttable is 1.6616, there is a partially significant effect on employee job satisfaction between motivation (X3) in Jakarta BPAD DKI. A simultaneous test (F-test) showed Fcount 17.105 and Ftable 2.70. This can be interpreted that culture (X1), environment (X2), and motivation (X3) together have a significant effect on the job satisfaction of Jakarta BPAD DKI employees. This study was conducted with Other Service Providers and local officials of the DKI Jakarta Regional Wealth Management Agency, and further studies may be conducted by other companies. No one has specifically investigated public officials from other private service providers (PJLPs) of the Jakarta Regional Wealth Management Agency DKI.